Upgrading Melanoma Treatment: Promising Immunotherapies Combinations in the Preclinical Mouse Model - Lara-Vega, Israel (Current Cancer Therapy Reviews, 2024)
Background: Melanoma, known for its high metastatic potential, does not respond well to existing treatments in advanced stages. As a solution, immunotherapy-based treatments, including anti-PD-1/L1 and anti-CTLA-4, have been developed and evaluated in preclinical mouse models to overcome resistance. Although these treatments display the potential to suppress tumor growth, there remains a crucial requirement for a thorough assessment of long-term efficacy in preventing metastasis or recurrence and improving survival rates. Methods: From 2016 onwards, a thorough examination of combined immunotherapies for the treatment of cutaneous melanoma in preclinical mouse models was conducted. The search was conducted using MeSH Terms algorithms in PubMed®, resulting in the identification of forty-five studies that met the rigorous inclusion criteria for screening. Results: The C57 mouse model bearing B16-melanoma has been widely utilized to assess the efficacy of immunotherapies. The combination of therapies has demonstrated a synergistic impact, leading to potent antitumor activity. One extensively studied method for establishing metastatic models involves the intravenous administration of malignant cells, with several combined therapies under investigation. The primary focus of evaluation has been on combined immunotherapies utilizing PD- 1/L1 and CTLA-4 blockade, although alternative immunotherapies not involving PD-1/L1 and CTLA-4 blockade have also been identified. Additionally, the review provides detailed treatment regimens for each combined approach. Conclusion: The identification of techniques for generating simulated models of metastatic melanoma and investigating various therapeutic combinations will greatly aid in evaluating the overall systemic efficacy of immunotherapy. This will be especially valuable for conducting short-term preclinical experiments that have the potential for clinical studies.
Keywords: combined treatments